Sleep and Diet: Mounting Evidence of a Cyclical Relationship - Zuraikat, Faris M; Wood, Rebecca A; Barragán, Rocío; St-Onge, Marie-Pierre (Annual review of nutrition, 2021)
Two factors intrinsic to health are diet and sleep. These two behaviors may well influence one another. Indeed, that insufficient sleep adversely impacts dietary intakes is well documented. On the other hand, diet may influence sleep via melatonin and its biosynthesis from tryptophan. Experimental data exist indicating that provision of specific foods rich in tryptophan or melatonin can improve sleep quality. Whole diets rich in fruits, vegetables, legumes, and other sources of dietary tryptophan and melatonin have been shown to predict favorable sleep outcomes. Although clinical trials are needed to confirm a causal impact of dietary patterns on sleep and elucidate underlying mechanisms, available data illustrate a cyclical relation between these lifestyle factors. We recommend adopting a healthful diet to improve sleep, which may further promote sustained favorable dietary practices.